FRACTURE TOUGHNESS OF HSLA WELDS MADE ON PENSTOCK MATERIAL - Praunseis, Zdravko (Journal of Energy Technology, 2024)
The presence of different microstructures along the pre-crack fatigue front has a significant effect on the critical crack tip opening displacement (CTOD). This value is the relevant parameter for the safe servicing of welded structures (penstocks). In the case of specimens with the through-thickness notch partly in the weld metal, partly in the heat-affected zone, and partly in the base material, i.e., using the composite notched specimen, the fracture behaviour significantly depends on the portion of the ductile base material, the size, and the distribution of mismatching factor along the vicinity of the crack front.